2021
DOI: 10.1108/jic-09-2020-0306
|View full text |Cite
|
Sign up to set email alerts
|

Does intellectual capital have any influence on stock price crash risk?

Abstract: PurposeThis paper explores the influence between intellectual capital (IC) and the risk of stock price crashes by using company performance as an intervening variable.Design/methodology/approachThis study empirically analyzes the impact of the efficiency of IC on stock price crash risk using a sample size of 152 companies listed on the Indonesia Stock Exchange (IDX) during 2018. To test the research hypotheses, regression analysis and path analysis were applied. In addition, the researchers added exploration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…Value Added Intellectual Capital (VAICTM) has a probability value of 0.8180 > 0.05, therefore H1 is rejected, meaning that Value Added Intellectual Capital does not affect stock prices in the KBMI III and KBMI IV category banks for the period 2017 -2022. This research result is consistent with (Safitri et al, 2020), (Farhanah & Mutasowifin, 2022), (Fatimah & Bagasworo, 2021), (Dani Yudhitya & Agustina Prihastiwi, 2023), and (Probohudono et al, 2022). However, this research differs from studies by (Handayani & Karnawati, 2021), (Safira et al, 2023), (Sunardi et al, 2019), and (Agustin, 2023) which state that Value Added Intellectual Capital affects Stock Prices.…”
Section: The Influence Of Value Added Intellectual Capital (Vaictm) O...supporting
confidence: 85%
“…Value Added Intellectual Capital (VAICTM) has a probability value of 0.8180 > 0.05, therefore H1 is rejected, meaning that Value Added Intellectual Capital does not affect stock prices in the KBMI III and KBMI IV category banks for the period 2017 -2022. This research result is consistent with (Safitri et al, 2020), (Farhanah & Mutasowifin, 2022), (Fatimah & Bagasworo, 2021), (Dani Yudhitya & Agustina Prihastiwi, 2023), and (Probohudono et al, 2022). However, this research differs from studies by (Handayani & Karnawati, 2021), (Safira et al, 2023), (Sunardi et al, 2019), and (Agustin, 2023) which state that Value Added Intellectual Capital affects Stock Prices.…”
Section: The Influence Of Value Added Intellectual Capital (Vaictm) O...supporting
confidence: 85%
“…On the other hand, researchers take the fundamental analysis hypothesis, engaging it with a resource base view and asymmetric information theory to reveal the determinants of PCR from an organization's fundamental variables. The empirical studies test the effect of climate change disclosure (Lin and Wu, 2023), ESG (Gao et al ., 2022), intellectual capital (Probohudono et al ., 2021), local CEO's ability (Chen et al ., 2022a), political orientation (Chen et al ., 2022b) and product market competition (Benkraiem et al ., 2022) on PCR. It is in line with Jin and Myers (2006), who suggested that companies may be incentivized to withhold bad news to absorb certain downside risks.…”
Section: Literature Reviewmentioning
confidence: 99%